Tail risk and asset prices in the short-term - Almeida, Caio; Freire, Gustavo; Garcia, René; Hizmeri, Rodrigo (Review of Finance, 2026)
Abstract We combine high-frequency stock returns with risk-neutralization to extract the daily common component of tail risks perceived by investors in the cross-section of firms. Our tail risk measure significantly predicts the equity premium and variance risk premium at short horizons. Furthermore, a long–short portfolio built by sorting stocks on their recent exposure to tail risk generates abnormal returns with respect to standard factor models. Incorporating investors’ preferences via risk-neutralization is fundamental to our findings: the predictive power of the physical tail risk is weaker and generally subsumed by its risk-neutral counterpart.